Introduced Opuntia spp. in Madagascar : problems and opportunities - Larsson, Per (SLU/SLU External Relations, 2004)
Several Opuntia species have been introduced to southern Madagascar and are today affecting the local economy. Especially the species Opuntia stricta has been recorded as a dangerous weed. The information about which species that are present and how they are affecting the life of the people in southern Madagascar has not earlier been described. In this study this information was collected using a semi-structured, open-ended interview technique. The aim was to describe how the Opuntia species are affecting the human livelihood and to describe the economical and nutritional importance of Opuntia spp. in ten study sites located in the Androy region in south Madagascar. In total 27 different Opuntia variants with local names was recorded and six of them was present in all study sites. Two species were having more impact than the others: 1) O. ficus-indica which fruit is an important food resource for humans and the cladodes are given as fodder to the livestock. 2) O. stricta which is a serious weed strongly affecting the economy and livelihood negatively in this region. The effect of O. stricta can be summarised in three categories: i) a weed problem. ii) loss in livestock. iii) a health problem. The important pastoralism in Androy is today highly depended to O. ficus-indica but seriously threatened by O. stricta.